2019
DOI: 10.1017/cjn.2019.37
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Damage in the Semantic Variant of Primary Progressive Aphasia

Abstract: ABSTRACT:Background: The semantic variant of primary progressive aphasia (svPPA) is a form of dementia, mainly featuring language impairment, for which the extent of white matter (WM) damage is less described than its associated grey matter (GM) atrophy. Our study aimed to characterise the extent of this damage using a sensitive and unbiased approach. Methods: We conducted a between-group study comparing 10 patients with a clinical diagnosis of svPPA, recruited between 2011 and 2014 at a tertiary reference cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…Additionally, a recent study showed that tracts, such as the uncinate fasciculus, the superior longitudinal fasciculus, the retrolenticular part of internal capsule, the inferior frontooccipital fasciculus, posterior thalamic radiation, and posterior corona radiata are associated with this stream (70). Similarly, other studies supported alterations in white matter in uncinate (18, 54, 56), inferior longitudinal fasciculi (55, 57, 61, 71) Patients with svPPA have impaired comprehension of content words (nouns, verbs, adjectives), anomia, and semantic impairment (4, 72).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Additionally, a recent study showed that tracts, such as the uncinate fasciculus, the superior longitudinal fasciculus, the retrolenticular part of internal capsule, the inferior frontooccipital fasciculus, posterior thalamic radiation, and posterior corona radiata are associated with this stream (70). Similarly, other studies supported alterations in white matter in uncinate (18, 54, 56), inferior longitudinal fasciculi (55, 57, 61, 71) Patients with svPPA have impaired comprehension of content words (nouns, verbs, adjectives), anomia, and semantic impairment (4, 72).…”
Section: Discussionmentioning
confidence: 56%
“…Accordingly with gray matter analysis in our study svPPA patients had a bilateral atrophy in temporal regions with more left sided involvement in comparison with bvFTD and controls. Bilateral atrophy in svPPA has been reported previously both gray and white matter analysis (25, 56). Additionally, both hemispheres underpinned the semantic and conceptual representations (75), which are affected in svPPA.…”
Section: Discussionmentioning
confidence: 62%
“…This tract’s connection to the ATL also brings up the possibility of involvement in semantic processing. Generally aligned with a role in semantic processing, UF deficits are often observed in dementia, including the semantic variant of PPA (Agosta et al, 2013 ; Powers et al, 2013 ; Iaccarino et al, 2015 ; Tu et al, 2016 ; Briggs et al, 2018a ; Bouchard et al, 2019 ), with some studies claiming decreased FA of the UF to be the main predictor of semantic dementia (Agosta et al, 2012 ; Bouchard et al, 2019 ), and others showing a correlation between cognitive decline and the integrity of the UF (Morikawa et al, 2010 ; Hiyoshi-Taniguchi et al, 2015 ). Moreover, the UF has been implicated, along with IFOF, in several studies that have used a battery to tap into semantic processing (de Zubicaray et al, 2011 ; Mirman et al, 2015 ; see also semantic processing deficits in schizophrenia; Surbeck et al, 2020 ).…”
Section: Uncinate Fasciculus (Uf)mentioning
confidence: 99%
“…This tract's connection to the ATL also brings up the possibility of involvement in semantic processing. Generally aligned with a role in semantic processing, UF deficits are often observed in dementia, including the semantic variant of PPA (Agosta et al, 2013;Bouchard et al, 2019;Iaccarino et al, 2015;Powers et al, 2013;Tu et al, 2016), with some studies claiming decreased FA of the UF to be the main predictor of semantic dementia (Agosta et al, 2012;Bouchard et al, 2019), and others showing a correlation between cognitive decline and the integrity of UF (Hiyoshi-Taniguchi et al, 2015;Morikawa et al, 2010). Moreover, UF has been implicated, along with IFOF, in several studies that have used a battery to tap into semantic processing (de Zubicaray et al, 2011;Mirman et al, 2015; see also semantic processing deficits in schizophrenia; Surbeck et al, 2020 ).…”
Section: Uncinate Fasciculus (Uf)mentioning
confidence: 99%